Random mating and reproductive compatibility among Argentinean and southern Brazilian populations of Anastrepha fraterculus (Diptera: Tephritidae) - Rull, J. (2012)
As a prerequisite for area-wide application of the sterile insect technique in an area encompassing northern Argentina and southern Brazil, prezygotic and postzygotic reproductive compatibility among three geographically distant populations in the area was tested. In field cages, sexually mature adults of each population were found to be sexually compatible, mating duration was not affected by fly origin and there was no clear evidence of spatial partition of mating location. In the laboratory, homotypic and heterotypic crosses for all possible combinations displayed similar levels of fertility and yielded F1 adults without distortion of the sex ratio. Finally, F1 hybrid and parental adults produced equally viable F2 eggs. Put together, our results and those from earlier studies suggest that a large area, ranging from Buenos Aires to the surroundings of São Paulo, could be managed using a single A. fraterculus mass-reared strain. At the northern margin of this area, two A. fraterculus morphotypes appear to coexist in sympatry. We delineate future research to further delimit the distribution of the aff1 morphotype (Argentina-southern Brazil) and to gain insight into evolutionary patterns producing divergence and radiation of tropical fruit fly species.